Age determination of a long-lived coregonid from the Canadian North: comparison of otoliths, fin rays and scales in inconnu (Stenodus leucichthys) - Gendron, M.; Tonn, W.M.; Howland, K.L.; Tallman, R.F. (2004)
We examined otoliths, pelvic fin rays and scales of inconnu to determine precision of age estimates within and between readers, and to compare relative accuracy of estimates from different structures. Our main objective was to determine if readability and estimates from fin rays and scales, which can be non-lethally removed, were similar to those of otoliths, which are generally considered the most reliable ageing structure. Among- and within-reader variation was low for both fin rays and otoliths, but higher for scales. Variation tended to increase with fish length for all structures. Scales were most difficult to read and had age estimates that were significantly lower than the other structures at ages of ten years and greater. Age estimates and readability of fin rays and otoliths were similar.